(untitled) (Economic and Political Thought, 2018)
Thanks to the archival sources that have not been used so far, the article provides an opportunity to look at the mechanism of freeing Poland and, in a broader perspective, other countries that have been under the Soviet influence since Yalta, from the hegemony of the USSR. Against this background, it presents the opinions and intentions of the communists who lost power as a result of the election of 4 June 1989. They pinned their hopes on Wojciech Jaruzelski, the President whom the amended Constitution gave great powers. However, life showed that he could have exercised them only for the price of the country division, a conflict that would have led to chaos instead of reforms, a breakdown instead of strengthening Poland’s position on the international arena. It would have strongly established Jarulelski’s negative image, too. The President faced a dilemma: support changes, including those that were geopolitical in nature, or oppose them. Having recognised the interest of the state and the will of the citizens expressed in the election, he chose the first option. However, it must be said that his weakening political position played an important role. The presidential ballot won by one vote, systematic elimination of the PUWP representatives from posts in the coalition government, the collapse of PUWP, public opinion dislike – all these things deprived him of tools to act. In the relations with the USSR, he adopted a role of a buffer. Until the end of his term of office, however, he believed in the success of the Soviet perestroika and Gorbachev as a reformer of the system, which would continue existing after the transformation. That is why he wanted to support Gorbachev and use him as a guarantor of democracy at home as well as in international relations. He was afraid of the USSR’s turn to nationalism and rowdy imperialism. He could not realise Poland’s turn from the East to the West, accession to NATO and the European Communities. However, he did not undertake any steps that might have destroyed those plans.